Pengaruh Beban Kerja, Konflik Peran Ganda, dan Dukungan Sosial Keluarga terhadap Stres Kerja pada Karyawan Wanita yang Telah Menikah - Supriyati Supriyati; Vira Sandayanti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
The increasing participation of women in the workforce presents various challenges, particularly in balancing family and work pressures, which can lead to work-related stress. This study was conducted to examine the effects of workload, dual-role conflict, and family social support on work-related stress among female employees. The research hypothesis posits that there is a significant relationship between workload, dual-role conflict, and family social support and work-related stress. A quantitative approach was used in this study, with a total of 188 female employees who were married, had children, were aged 25–55 years, and had a minimum of 1 year of work experience. Subjects were selected using simple random sampling. Data were collected using the work stress scale, work load scale, dual role conflict scale, and family social support scale. Multiple regression analysis was conducted using IBM SPSS Statistics. The results indicate that workload, dual-role conflict, and family social support simultaneously have a significant effect on work-related stress, accounting for 51.0% of the variance. Partially, workload and dual-role conflict have a significant positive effect on work-related stress, while family social support has a significant negative effect on work-related stress. These findings highlight the importance of workload management, work-family balance, and strengthening family support in reducing work-related stress among female employees.